The Future Workforce of the Environmental Laboratory. Issue 3 (5th April 2023) - Adams, Hunter; Morin, Erin; Holloway, Nicole; Cottrell, Ashley; Thames, Becky; Gillis, Leah; Wangsness, Kathryn; Loudon, Jennifer; Wright, Sarah
Key Takeaways: The environmental laboratory workforce is aging out and needs creative solutions to recruit and retain skilled staff to perform physical, microbial, chemical, and radiological tests. There are immediate needs for chemists to work in radiochemistry and to conduct analyses for per‐ and polyfluoroalkyl substances and other contaminants of emerging concern. Promoting the water and wastewater industry and developing the industry workforce require education through public outreach, internships, fellowships, and citizen science.